MODEL AUDIT PEMERINTAHAN YANG MEMPUNYAI IMPLIKASI TERHADAP KUALITAS AKUNTABILITAS KEUANGAN INSTANSI PEMERINTAH DAERAH - Dadang Sadeli (Media Riset Akuntansi, Auditing & Informasi, 2009)
The research studies and examines about government audit model and implication on quality of local government agency financial accountability. The study was conducted by survey method. The size of samples was 150 official local Municipal Government and Regency's official offices in West Java Province area. The analysis method used in this research was descriptive analysis with the analysis tool using the Structural Equation Modeling (SEM).Rresearch findings: (1) accomplishment of government audit may significantly be explained by financial audit, performance audit, and investigation audit, (2) quality of local government agency financial accountability significantly may be accounted for by financial accountability containing a financial responsibility in keeping with government program and activity, financial accountability containing financial performance evaluation, financial accountability that was built on the basis of reliable information system, objective and independent evaluation on financial accountability, follow-up of assessment report on financial accountability, (3) implementation of government audit has implication on quality of local government agency financial accountability.Keywords: government audit, financial audit, performance audit, and investigation audit, and quality of local government agency financial accountability.